(untitled) (Scientific journal of the Fergana State University, 2023)
One of the important representatives of metallocenes is the practical significance of biologically active compounds derived from ferrocene in the chemical industry, medicine, pharmacology, as well as the synthesis of o-ferrocenylbenzoic acid with amygdalin ([(6-O-β-D-glucopyranosyl-4-O-(o-ferrocenylbenzoyl)β-D-glucopyranosyl)oxy](phenyl)acetonitrile), reaction with monomethylolurea and reaction product of 1-2-carboxyperphenyl)-1’-N-methyloxyferrocenylamide IR, mass spectroscopic analysis, data on study of the biological activity of its water-soluble salts.